Bahasa Persuasi pada Iklan Kosmetik di Aplikasi Tiktok - Yuwana Yuwana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article discusses the use of persuasive language in cosmetic advertisements on the TikTok application. Persuasion is a text that aims to invite or persuade others to take a certain action. In other words, Persuasion is used to convey a certain Intention so that the audience can carry out or accept the ideas of the author of the text. This means that persuasive writing has the ability to generate certain stimuli that are important to the author. In this study, the researcher chose a qualitative method to conduct research on the use of persuasive language in cosmetic advertisements on the TikTok application. In data collection, researchers used techniques such as capturing images, listening, and taking notes. The data used in this study were cosmetic advertisements viewed on the TikTok application which included persuasive techniques. In this study, researchers found two of the seven types of persuasive language. There are two techniques used, namely rationalization which explains the content, and the results after using cosmetics and suggestions are influencing and persuading others to accept a certain position without providing a basis for trust.